Сходини сусідів на сільських кутках - "дернеците" - специфічна особливість спілкування болгарських переселенців у Бессарабії - Манолова, Г. (Народна творчість та етнографія, 2006)
The study off the neighbours' meetings is topical as it reveals the fact of preserving the settlers' connections with their motherland. The following research is based on the field materials gathered in 1999—2005 in Bulgarian villages on the border of Ukraine in Moldavia. Neighbours' meetings are a widespread form of informal communication in the village. It is a kind of entertainment, where people can talk and discuss their problems. The specific features of these meetings are depicted in the article as well.